Late blight control by using a decision support system in organic potato cultivation - Bangemann, Lars-W; Benker, M; Kleinhenz, B; Zellner, Michael; Bartels, Gerhard (MTT, 2007)
The late blight disease (Phytophthora infestans) is still regarded as an important yieldlimiting factor in the organic potato- production. Therefore the use of copper forms a crucial basis of the yield and quality- assurance. However, the copper enchrichment problems in the soil and their subsequently negative effects on non-target organisms appear to be on reason that a reduction of the copper-use is inevitable. For this reason, different strategies are developed for controlling the secondary-attack in the framework of the research project ÖKO-SIMPHYT. This project aims to achieve a sufficient control of the disease with less copper as possible. In the following, the results of the periods (2005 and 2006) out of a three year project are presented.
Keywords: Ka